Russia's Hybrid State and President Putin's Fourth-Term Foreign Policy. Issue 4 (4th July 2018) - Herd, Graeme P
Abstract : President Vladimir Putin's regime (individuals distributed across the normative state, parastate and oligarchic court) is focused on survival and self-preservation. Destabilisation of neighbours has represented a rational choice since 2007 and will continue to be the organising principle of Putin's fourth-term foreign policy (2018–24). In this article, Graeme P Herd discusses the logic that governs this power network and the dynamics that contribute to its evolution.